Ancient readings of Plato's Phaedo - Delcomminette, Sylvain.; Hoine, Pieter d'.; Gavray, Marc-Antoine. (Philosophia Antiqua, 2015)
Plato's Phaedo has never failed to attract the attention of philosophers and scholars. Yet the history of its reception in Antiquity has been little studied. The present volume therefore proposes to examine not only the Platonic exegetical tradition surrounding this dialogue, which culminates in the commentaries of Damascius and Olympiodorus, but also its place in the reflections of the rival Peripatetic, Stoic, and Sceptical schools. This volume thus aims to shed light on the surviving commentaries and their sources, as well as on less familiar aspects of the history of the Phaedo 's ancient reception. By doing so, it may help to clarify what ancient interpreters of Plato can and cannot offer their contemporary counterparts.